Inclusive smart cities? Technology-driven urban development and disabilities - Makkonen, Teemu; Inkinen, Tommi (Elsevier Ltd, 2026)
The concept of smart cities refers to urban areas that utilize (digital) technologies to enhance urban operations, services, and the quality of life of their residents. However, people have varying possibilities and capabilities for using (digital) technologies. This intertwines the technology-driven urban development with the ideal of inclusiveness (or the lack thereof) as it seems unrealistic to assume that smart cities would benefit equally the whole society. This controversy is approached by questioning whether smart cities can really improve the living conditions of the disadvantaged via reviewing the literature that ties technology-driven urban development to persons with disabilities. The study shows, first, that disabilities are rarely discussed in the extant literature on smart cities particularly from a critical perspective. Second, it is underlined here, based on the reviewed literature, that while smart city initiatives hold promise for enhancing urban living conditions of persons with disabilities, they are not one-size-fits-all answers to tackle the marginalization of persons with disabilities. Rather, since technological solutions do not counter the fundamental barriers of exclusion, urban technologies still need advanced ideas in establishing a truly inclusive smart city.